A Mechanistic Overview of Taste Bud Maintenance and Impairment in Cancer Therapies() - Gaillard, Dany (Chem Senses, 2021)
Since the early 20th century, progress in cancer therapies has significantly improved disease prognosis. Nonetheless, cancer treatments are often associated with side effects that can negatively affect patient well-being and disrupt the course of treatment. Among the main side effects, taste impairment is associated with depression, malnutrition, and morbid weight loss. Although relatively common, taste disruption associated with cancer therapies remains poorly understood. Here, we review the current knowledge related to the molecular mechanisms underlying taste maintenance and disruption in the context of cancer therapies.